Begutachtung von Prothesenversorgungen der unteren Extremität - Schwarze, Martin; Alimusaj, Merkur; Heitzmann, Daniel; Block, Julia; Putz, Cornelia; Wolf, Sebastian Immanuel; Schiltenwolf, Marcus (Der Orthopäde, 2020)
Although the number of major amputations is declining throughout Germany, more than 57,000 surgical procedures for amputation still take place. As a consequence of high prosthetic care costs, these often lead to disputes before the social court in which expert medical opinions are required. With knowledge of the legal norms, the remit of the expert opinion can be fulfilled. The expert begins with evaluation of the patient's file and a search of the contested parts. The investigation includes a medical history, in addition to a physical examination, in order to be able to comment on the disputed beneficial use of the therapeutic appliance and respond to questions of proof. Questionnaires may be helpful.
Zusammenfassung in englischer Sprache: Expert assessment of lower extremity prosthetics
Online publiziert:14. Mai 2019
Gesehen am 01.04.2020